Age components of queen retinue workers in honeybee colony (Apis mellifera) - Yi, Yao; Li, You; Zeng, Zhijiang (Sociobiology, 2016)
It’s known that elaborate age is closely associated with polyethism in honeybee colonies, and the circle composed of queen retinue workers is a usual phenomenon in honeybee colonies. In this study, we showed that the age-bracket of retinue workers is 2-23d, but mainly 6-18d by marking newly hatched workers in two colonies.